Development and experimental evaluation of bio-inspired pile surface asperities for enhanced load transfer in sandy soils - Candra, Agata Iwan; Munawir, As`ad; Zaika, Yulvi; Suryo, Eko Andi (Eastern-European Journal of Enterprise Technologies, 2025)
In sandy soils, skin resistance efficiency is critical, as it governs load capacity, settlement, and foundation cost. This study investigates pile foundations with directional surface asperities embedded in uniform sand to clarify the limited knowledge of how asperity orientation (cranial vs. caudal), geometric ratio (L / H), and pile diameter affect axial load transfer. Experimental tests were conducted on steel piles with diameters of 10, 12, and 15.85 mm under smooth, cranial, and caudal conditions with L / H ratios of 20, 26.67, and 33.33. Axial compression tests following ASTM D1143-20 in controlled dry sand provided ultimate load and shaft resistance data, validated by one-way ANOVA. The results show that cranial asperities consistently outperformed other surfaces, with the Cr L / H 20 configuration on the 15.85 mm pile reaching 0.368 kN, a 392.51% increase over smooth piles, while caudal asperities achieved only 134.30%. Cranial asperities also mobilized shaft resistance more uniformly along the pile, reducing end-bearing reliance. This performance is explained by stronger passive interaction at the pile-soil interface, which raises normal stress and friction mobilization. The distinctive feature of this research is the identification of the L / H ratio as a measurable design parameter, with L / H = 20 found to be optimal, in contrast to previous studies that described roughness only qualitatively. The findings demonstrate practical potential for applying cranial asperity designs in pile foundations for light- to medium-scale infrastructure on sandy soils, such as bridges, wharves, and transmission towers, enabling shorter or fewer piles without compromising safety while improving cost efficiency and geotechnical performance